2013
DOI: 10.1007/s11434-013-5925-9
|View full text |Cite
|
Sign up to set email alerts
|

Deleting a marked state in quantum database in a duality computing mode

Abstract: In this article, we present a deletion algorithm in the duality computer that deletes a marked state from an even superposition of all basis-states with certainty. This duality computer deletion algorithm requires a single query, and this achieves exponential speedup over classical algorithm. Using a duality mode and recycling quantum computing, we provide a realization of this duality computer deletion algorithm in quantum computer. duality computer, deletion algorithm, search algorithm, database, recycling q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…From Fig. 2, the corresponding CS gate requires one iSWAP gate and plus additional four single-qubit rotatins, which can be constructed as (6). The single-qubit gate operations required for implementing quantum cloning in Fig.…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From Fig. 2, the corresponding CS gate requires one iSWAP gate and plus additional four single-qubit rotatins, which can be constructed as (6). The single-qubit gate operations required for implementing quantum cloning in Fig.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…It is impossible to clone or delete a quantum state by linearity of quantum theory, so the approximate cloning and deleting of quantum states has become the main objectives of the study in the future. There has been great interest recently on the clone and deletion of quantum states [5][6][7][8]. The approximate quantum cloning [2] including universal quantum cloning (UQC) [9][10][11][12], phase-covariant cloning (PCC) [13][14][15], real state cloning (RSC) [16][17][18], economical phase-covariant cloning (EPCC) [19][20][21], and economical real state cloning (ERSC) [22,23] working without ancillary has been lucubrated.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, entanglement is required in nearly all quantum communication and computation protocols [3], such as quantum teleportation [4][5][6][7], dense coding [8,9], quantum key distribution (QKD) [10][11][12], quantum secure direct communication [13][14][15], quantum computation [16][17][18][19], and other protocols [20][21][22][23]. During the past decade, with the rapid development of the experimental process on quantum control, there is a rapidly growing interest in entanglement generation [24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of duality quantum computers is first proposed by Long in 2002 based on the general principle of quantum interference 17 18 , which draw many attentions 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 . It is shown that any bounded linear operator can be expressed as a linear combinations of unitary operators in a duality quantum computer 21 .…”
mentioning
confidence: 99%